2007
DOI: 10.1111/j.1365-2966.2007.12422.x
|View full text |Cite
|
Sign up to set email alerts
|

Q2237+0305 source structure and dimensions from light-curve simulation

Abstract: Assuming a two-component quasar structure model consisting of a central compact source and an extended outer feature, we produce microlensing simulations for a population of compact masses in the lensing galaxy of Q2237+0305. Such a model is a simplified version of that adopted to explain the brightness variations observed in Q0957. The microlensing light curves generated for a range of source parameters were compared to the light curves obtained in the framework of the Optical Gravitational Lensing Experiment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 54 publications
(102 reference statements)
3
22
0
Order By: Relevance
“…The S‐S model calculations do not incorporate any influence from the dusty torus region and cannot therefore naturally reproduce the amplitude of the variability or the rapidity. The results of the study with unbiased calculations and unrestricted accretion disc sizes and allowing for the fractional contribution from dusty torus emission/reflection (Vakulik et al 2007) quite naturally match the amplitudes, durations and lensed fractions of the luminosity. The detection of reverberation between the luminous inner structure, presumably the inner edge of the accretion disc as in the S‐S model, and a large outer region would strongly favour limiting the S‐S model to the description of the inner luminosity only.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The S‐S model calculations do not incorporate any influence from the dusty torus region and cannot therefore naturally reproduce the amplitude of the variability or the rapidity. The results of the study with unbiased calculations and unrestricted accretion disc sizes and allowing for the fractional contribution from dusty torus emission/reflection (Vakulik et al 2007) quite naturally match the amplitudes, durations and lensed fractions of the luminosity. The detection of reverberation between the luminous inner structure, presumably the inner edge of the accretion disc as in the S‐S model, and a large outer region would strongly favour limiting the S‐S model to the description of the inner luminosity only.…”
Section: Introductionmentioning
confidence: 69%
“…An initiating pulse with a characteristic duration of 50 proper days is followed by successive brightness features having longer durations, as would be expected if the reverberation region were of size comparable to or somewhat larger than the initiating region. The general pattern of four pulses sequenced as expected for the Elvis surface geometry is normally observed, and it is therefore unsurprising that studies of quasar microlensing have already shown that an inner structure having size scale expected for the accretion disc inner edge gives a microlensing pulse of only one‐third of the expected amplitude, which has already been interpreted to imply that outer luminous structure must contribute to the quasar’s continuum emission (Schild 1996; Vakulik et al 2007).…”
Section: Estimation Of Quasar Viewing Anglesmentioning
confidence: 82%
“…), and this model will agree with the available data provided that an appropriate source size is chosen. On the other hand, a number of authors [4,16,[33][34][35][36][37][38][39] discussed delicate questions concerning determination a fine quasar structure from HAE. For example, the authors of [36] wrote that the GLITP data [28] on Q2237+0305 admit only accretion disc models (see also [4,39]).…”
Section: Preliminary Commentsmentioning
confidence: 99%
“…We note that since the work by Kochanek [37], followed by a number of authors [4,35,[38][39][40][41][42], statistical methods dealing with the complete light curves of the GLS images have been developed. This approach is very attractive because it allows to take into account the whole aggregate of observational data on image brightness variations yielding estimates of the microlens masses and source model parameters.…”
Section: Preliminary Commentsmentioning
confidence: 99%
See 1 more Smart Citation